The sorption and short-term immobilization of lead and cadmium by nano-hydroxyapatite/biochar in aqueous solution and soil. (January 2022) - Zhou, Cailing; Song, Xin; Wang, Yiwei; Wang, Hui; Ge, Shifu
Abstract: In this study, the composite materials using different ratios of biochar (BC) to nano-hydroxyapatite (nHAP) were prepared for the remediation of lead (Pb) and cadmium (Cd) contaminated water and soil. The sorption and the immobilization experiments indicated a higher sorption capacity and immobilization efficiency of Pb compared to those of Cd. The characteristics of XRD, FTIR, SEM, and XPS manifested that dissolution-precipitation, cation exchange, complexation, and cation-π interaction were the main four mechanisms for the sorption of Pb 2+ and Cd 2+ using composite material PC1 (nHAP/BC = 1/1). From semi-quantitative analysis, the mineral effect accounted for the majority of the immobilization of Pb and Cd. Due to obvious Pb-precipitates in the sorbed material, dissolution-precipitation primarily affected the sorption of Pb using PC1, while the immobilization of Cd was mainly attributable to cation exchange. Such results corresponded to the stable Pb-precipitates and unstable Cd-compounds in soil, among which the latter was prone to be released into the environment. The sorption capacity in aqueous solutions and the immobilization efficiencies in the soil for both Pb and Cd increased with the addition of nHAP, which were linearly correlated to the nHAP proportion in the composite materials. In future practical applications, the percentages of composite materials can be designed according to the specific pollutant concentration. This study sheds light on the explicit immobilization mechanisms for Pb and Cd in aqueous solutions to better understand their behaviors in the soil remediated by relevant materials. Graphical abstract: Image 1 Highlights: The sorption capacities were linearly correlated to the nHAP proportion in composite materials. Semi-quantitative analysis was conducted to strengthen the immobilization mechanism analysis. The interaction mechanisms for lead and cadmium in water affected the stabilization in the soil. The immobilization of lead was primarily controlled by the dissolution-precipitation. The immobilization of cadmium was mainly attributable to the cation exchange.